2019
DOI: 10.4067/s0718-19572017000100016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of swordfish Xiphias gladius and blue shark Prionace glauca fisheries by Catalan longline fleet from 2010 to 2015 in the occidental Mediterranean Sea

Abstract: Análisis de la explotación del pez espada

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In contrast, the current mass (and size) of swordfish caught in the central Southeast Pacific (FAO fishing subarea 87.2) is mainly between 20 and 150 kg, despite the use of modern fishing techniques (Cerna, 2009). This mean-size difference may illustrate the fishing pressure and deterioration of the stock status of swordfish in the Southeastern Pacific in modern times (see Biton-Porsmoguer, 2017;Siskey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the current mass (and size) of swordfish caught in the central Southeast Pacific (FAO fishing subarea 87.2) is mainly between 20 and 150 kg, despite the use of modern fishing techniques (Cerna, 2009). This mean-size difference may illustrate the fishing pressure and deterioration of the stock status of swordfish in the Southeastern Pacific in modern times (see Biton-Porsmoguer, 2017;Siskey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in the Mediterranean have already indicated the pressure being placed on particular vulnerable benthic species by coastal small-scale and recreational fisheries (Marengo et al, 2015;Harmelin et al, 2015;Adbul Malak, 2011;Biton-Porsmoguer, 2017;Biton-Porsmoguer and Lloret, 2018).. For example, Marengo et al (2015) found that the combined impact of artisanal and recreational fishing targeting vulnerable species can have consequences on the D. dentex stock in the Bonifacio Strait Natural Reserve.. In addition, the status of the main large pelagic species fished offshore, such as X. gladius and P. glauca, shows clear signs of overexploitation (Biton-Porsmoguer, 2017;Biton-Porsmoguer and Lloret, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stock depletion, overfishing, and by-catch have decimated elasmobranch populations in the Mediterranean [17][18][19], with most species caught as valuable bycatch in trawl and net multispecies fisheries [20][21][22]. Oceanic pelagic sharks are threatened by surface longlining targeting species, such as swordfish and tuna [23,24], worsening the situation of pelagic sharks, such as white sharks (Carcharodon carcharias) and blue sharks (Prionace glauca) [19]. Shark Med, a Mediterranean NGO based in Mallorca (Spain), has developed and published innovative, non-invasive, and extended-time sub-surface BRUVs that repeatedly recorded sharks in open waters around the Balearic Islands [25].…”
Section: Introductionmentioning
confidence: 99%